A 3D cellular automata ore stockpile model – Part 1: Simulation of size segregation. (September 2022) - Ye, Z.; Hilden, M.M.; Yahyaei, M.
Highlights: A 3D dynamic model based on cellular automaton (CA) for modelling ore pile formation that incorporates size segregation is presented. Validation of model using industrial data demonstrated. The scale-up process for the model using experimental data is explained. Abstract: This paper describes a 3D cellular automaton (CA) for modelling ore pile formation that incorporates size segregation due to surface stratification. Ore stockpiles and bins are essential in mining operations as a buffer between the mine and the mineral processing plant, and their operation plays an important role in the overall performance of the downstream equipment. Size segregation can occur if the feed size to the pile varies over time or due to a variety of segregation mechanisms occurring in the pile itself. In particular, it can occur as a result of percolation stratification within surface flows. The structure of the newly developed CA model is described, and the simulated surface profile and size segregation response is validated through a series of laboratory-scale piles for characterizing the segregation potential of the feed particles. It is found that the model adequately describes the segregation behaviour at a range of model scales where coarse particles roll to the outside of the pile and fine particles are concentrated around the centre of the pile. Moreover, it is found that the model is sufficiently fast to use in real-time applications such as dynamic process control and digital twins.